2009
DOI: 10.1016/j.jcrs.2009.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Photorefractive keratectomy in the management of refractive accommodative esotropia in young adult patients

Abstract: Photorefractive keratectomy was effective in the treatment of purely accommodative esotropia in young adult patients at a follow-up of 1 year. There were no cases of visual acuity loss or complications from the laser treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 8 publications
0
21
0
3
Order By: Relevance
“…SA for accommodative esotropia is also having some success. Pacella reported orthophoria in 12 out of 15 patients with the remaining 3 having a reduction in the angle of deviation with an excellent refractive outcome with a mean spherical equivalent postoperatively of −0.01 D 105 . The results of hyperopic SA remain less accurate than those of myopic SA but continue to evolve.…”
Section: Discussionmentioning
confidence: 99%
“…SA for accommodative esotropia is also having some success. Pacella reported orthophoria in 12 out of 15 patients with the remaining 3 having a reduction in the angle of deviation with an excellent refractive outcome with a mean spherical equivalent postoperatively of −0.01 D 105 . The results of hyperopic SA remain less accurate than those of myopic SA but continue to evolve.…”
Section: Discussionmentioning
confidence: 99%
“…Pacella et al 6 have treated 15 subjects by PRK and, after a one-year follow-up, 12 patients were orthophoric and three patients had a reduction in the angle of deviation. Nucci et al 7 treated 40 patients by PRK with a mean follow-up of 3.6 years and all subjects were orthophoric at final post-operative evaluations and visual acuity; refractive error and eye alignment remained constant after one-year post-operative examination.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there are some studies in the literature on treating refractive accommodative esotropia by photorefractive keratectomy (PRK) or laser in-situ keratomileusis (LASIK) with different results. [2][3][4][5][6][7] This study evaluates the effects of PRK among young patients with purely refractive accommodative esotropia.…”
Section: Introductionmentioning
confidence: 99%
“…↓BCVA in 3 eyes from 1990 to 2019 were selected, including 6 case reports [22][23][24][25][26][27] and 22 interventional case series [5,19,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Study Selectionmentioning
confidence: 99%
“…The follow-up period spanned between 6 and 126 months with all studies reporting mean follow-up periods of at least 12 months (Table 1). Surgical Technique PRK was the technique of choice in 7 studies [30,31,38,40,44,46,47], LASIK was performed in 8 studies [5,19,28,29,32,34,39,41], LASEK was reported in 1 study [5] and 3 studies implanted IOLs, including iris-fixated [36,41] and implantable collamer lens [45]. In 3 studies [35,37,43], both PRK and LASIK were used.…”
Section: Case Series Enrolling Adult Patientsmentioning
confidence: 99%